Blink reflex in progressive myoclonic epilepsies. (July 2015) - Coşkun, Tülin; Kiziltan, Meral; Gündüz, Ayşegül; Delil, Şakir; Yeni, Naz; Özkara, Çiğdem
Highlights: The R1 component of blink reflex was normal in progressive myoclonic epilepsy (PME). There were significantly prolonged latencies of the R2 and R2c in PME. There were also the reduced amplitudes of the R2 in PME. The disease duration and use of multiple antiepileptic drugs were related to abnormal R2s. There are abnormalities suppression of the R2 and R2c in PME. Abstract: Purpose: Progressive myoclonic epilepsies (PME) include a heterogeneous group of disorders. The brainstem is involved in these disorders, as demonstrated by neuroimaging and autopsy studies. The blink reflex (BR) is characteristically elicited after supraorbital electrical stimulation. The BR has two components, an ipsilateral R1 and bilateral R2 (R2 and R2c). The central generator of the BR is the brainstem. In this study, we aimed to investigate the functional status of the brainstem using the BR in PME cases with different etiological factors. Methods: We prospectively included 17 patients with a diagnosis of PME (8 male, 47.1%) who were examined between June 2009 and June 2012. For comparison, we included 41 healthy volunteers (18 male 43.9%) who did not have any neurological or systemic diseases. We recorded responses bilaterally over the orbicularis oculi muscles after supraorbital stimulation in all participants. Results: The R1 and R2 components of the BR were obtained in all healthy subjects with normal latencies, whereas abnormalities in the R2 and R2c components were observed at significantly higher rates in the PME patients. The mean latencies of the bilateral R2 and R2c components were significantly prolonged, and the amplitudes were diminished in the PME patients. Disease duration and the use of multiple antiepileptic drugs were related to abnormal R2s. Conclusion: The abnormalities of the R2 and R2c components of the BR confirmed the inhibition of the reticular formation. The findings are probably related to disease processes and partially due to the use of multiple antiepileptic drugs.